Analisis Nilai Penting dalam Upaya Pelestarian Sumberdaya Arkeologi di Kawasan Pangkalan Militer TNI AU Haluoleo Desa Ranomeeto Kabupaten Konawe Selatan - Sunarto .; Abd. Rauf Suleiman; Syahrun . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
Archaeological resources in the Military Base Area of the Haluoleo Air Force have a diversity of Japanese residents' defense buildings in Kendari. But the threat of damage to archaeological resources is very potential caused by natural factors and human factors. Therefore, Archaeological resources should be carried out as soon as possible to avoid more serious damage. The problem in this research is that any archaeological resources are left behind, what important values are in the archaeological resources, and what preservation efforts should be done. The purpose of this research is to know the archaeological resources, the importance, and the preservation effort. Methods of research through collecting library data and field data (descriptions, photographs and interviews), then followed by analysis of important values of history, culture, science, education, and economics. The remains of archaeological resources in the TNI AU Haluoleo Military Base Area are bunker, revetment, ammunition warehouse, and archaeological resource structure in TNI AU Haluoleo Military Base has important historical, scientific, cultural, educational and economic value. Efforts to conserve archaeological resources in the region include physical and legal preservation. Physical preservation in the form of adaptation, restoration, reconstruction, rehabilitation, and consolidation. While from the law side is to provide legality of archaeological resources in the region. Keywords: archaeological resources, important values, the preservation effort